The Effect of Leadership Style, Loyalty and Employee Retention on Employee Performance at PT Herfinta Farm & Plantation - Putri Malaya; M. Chaerul Rizky; Saimara A. M Sebayang (Journal of Research in Social Science and Humanities, 2025)
This study aims to identify and analyze the influence of leadership style, loyalty, and employee retention on employee performance at PT Herfinta Farm Plantation. Employee performance is one of the key elements in achieving organizational goals. Leadership style refers to the way a leader influences employees to voluntarily engage in various joint actions, loyalty refers to employee commitment to the company, while employee retention represents the policies implemented by the company to retain skilled employees so that they remain committed to the organization. Data were collected through questionnaires distributed to 64 employees of PT Herfinta Farm Plantation. The analysis was conducted using multiple linear regression with SPSS Version 24.0. The results of the study indicate that leadership style, loyalty, and employee retention simultaneously have a significant influence on employee performance. Partially, leadership style contributes significantly to improving performance, loyalty also has a positive and significant impact on performance, and similarly, employee retention has a positive and significant influence. Therefore, it is recommended that companies pay more attention to the leadership style applied, the level of employee loyalty, and employee retention as key factors in improving employee performance